A nursing case management program in liver transplant - the screening criteria - Liliana Mota; Fernanda Bastos; Alice Brito (Instituto Politécnico de Viseu, 2022)
Introduction: Liver transplant is the last treatment in a situation of liver disease at an advanced stage. The case management is an important program in the promotion of the success of the liver transplant. Objective: To define the criteria of the screening phase for inclusion of a nursing case management program in patients who underwent a liver transplant. Methods: Longitudinal qualitative study via multi-case studies. We include six patients who underwent a liver transplant. Four participants are male, with an average age of 45 years. Data were collected through document analysis of the clinical process, participant observation and non-structured interviews. The data analysis was based on Strauss and Corbin's Grounded Theory. Results: We identified nine criteria of the screening phase: problematic or difficult experiences during the health/disease transition, lack of confidence in providers, socioeconomic problems, prolonged hospitalization, previous history of non-adherent therapeutic regime, excess or lack of health services' use, lower family support, psychiatric disease and symptoms of the disease. Conclusion: With the identification of these criteria, we may include the patients in a case management program and implement nursing therapeutics in response to their specific needs. This study is an important contribution to the clinical practice of nurses because it allows identifying the cases that are especially vulnerable, anticipating the patient's needs/difficulties in the health/disease transition process, and implementing therapeutics in response to the patients' real needs.